Employment Security - Lovell, Malcolm (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1989)
The authors is preoccupied with the performance of given societies in providing work opportunites for their citizens, and in developing private and public policies which contribute to employment security.